Aslam al-Silahdar Conservation and Documentation
The mosque of Aslam al-Silahdar was built in 1344 by a Mamluk prince and features jewel-toned inlaid marble and glittering glass mosaics. The American Research Center in Egypt (ARCE) and the Aga Khan Trust for Culture (AKTC) carried out the comprehensive conservation of the monument directed by Christophe Bouleau. ARCE and skilled laborers from the surrounding neighborhood worked on the structural and aesthetic conservation of the mosque.